STUDI PERBANDINGAN HASIL PERHITUNGAN PENGUKURAN C-STOK ANTARA PENGAMBILAN SAMPEL DESTRUKTIF DAN NON-DESTRUKTIF PADA TUMBUHAN SAGU DI TULEHU - Sehat Souwakil; Gun Mardiatmoko; Jan W. Hatulesila (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to compare the results of carbon stock (C-stock) calculations in sago palms using destructive and non-destructive methods, as well as to determine the starch yield of sago palms (Metroxylon sagu.) in Tulehu Village, Salahutu District, Central Maluku Regency. The study was conducted on five sago palms selected based on their size and growth phase, using a purposive sampling technique. The destructive method involved felling and weighing the actual biomass, while the non-destructive method used an allometric equation with parameters such as diameter, tree height, and wood specific gravity. The results showed that the destructive method produced an average carbon stock of 0.31 tons per tree, while the non-destructive method only produced 0.14 tons per tree, with an average difference of 0.17 and a deviation of 61.34%. This confirms that the non-destructive method tends to underestimate the actual value, so the destructive method remains more accurate and can be used as a basis for validation. Estimation of starch yield shows that one mature sago palm with a wet pith weight of 928 kg has the potential to produce 120.64–148.48 kg of dry starch and a yield of 13%–16%.